2014
DOI: 10.1371/journal.pone.0099204
|View full text |Cite|
|
Sign up to set email alerts
|

Beta- Lactam Antibiotics Stimulate Biofilm Formation in Non-Typeable Haemophilus influenzae by Up-Regulating Carbohydrate Metabolism

Abstract: Non-typeable Haemophilus influenzae (NTHi) is a common acute otitis media pathogen, with an incidence that is increased by previous antibiotic treatment. NTHi is also an emerging causative agent of other chronic infections in humans, some linked to morbidity, and all of which impose substantial treatment costs. In this study we explore the possibility that antibiotic exposure may stimulate biofilm formation by NTHi bacteria. We discovered that sub-inhibitory concentrations of beta-lactam antibiotic (i.e., amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 78 publications
(80 reference statements)
4
34
0
2
Order By: Relevance
“…Numerous studies have shown that b-lactams below their MIC (e.g. 1/4 and 1/2 MIC) could induce biofilm formation of different bacterial species (Ahmed et al, 2009;Davies et al, 2006;Frank et al, 2007;Gomes et al, 2013;Kaplan, 2011;Mirani and Jamil, 2011;Nucleo et al, 2009;Wu et al, 2014). Our findings demonstrated that 1/2 MIC of penicillin G induced biofilm formation in A. pleuropneumoniae.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Numerous studies have shown that b-lactams below their MIC (e.g. 1/4 and 1/2 MIC) could induce biofilm formation of different bacterial species (Ahmed et al, 2009;Davies et al, 2006;Frank et al, 2007;Gomes et al, 2013;Kaplan, 2011;Mirani and Jamil, 2011;Nucleo et al, 2009;Wu et al, 2014). Our findings demonstrated that 1/2 MIC of penicillin G induced biofilm formation in A. pleuropneumoniae.…”
Section: Discussionsupporting
confidence: 57%
“…Low concentrations of antibiotics including b-lactams can potentially function as signalling molecules and induce virulence, quorum sensing and biofilm formation (Andersson and Hughes, 2014;Kaplan, 2011;Wu et al, 2014;Yim et al, 2007). The mechanisms associated with these effects differ for each species, isolates and antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formation by NTHi has been identified as playing a key role in both colonization and disease, and it contributes to ineffective antibiotic treatment (28). NO has been shown to signal a dispersal response in several biofilm-forming species, rendering the released bacteria susceptible to antibiotics (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of exogenous indole or indole derivatives have a significant effect in the biofilm formation of both indoleproducing and nonindole producing bacteria and both Gram-negative and Gram-positive Escherichia coli Trancriptome Microarray Gene expression omnibus GSE3905 [84] Haemophilus influenzae Trancriptome Microarray Gene expression omnibus GSE58213 [85] Pseudomonas aeruginosa Trancriptome Microarray Gene expression omnibus GSE10030 [86] Staphylococcus epidermidis Trancriptome RNA-seq Gene expression omnibus GSE60834 [87] Vibrio cholerae Trancriptome Microarray Gene expression omnibus GSE42674 [88] Candida albicans, Streptococcus mutans Trancriptome Microarray Gene expression omnibus GSE52543 [89] Fusobacterium nucleatum, Streptococcus mutans, Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Streptococcus sanguinis Trancriptome Microarray Gene expression omnibus GSE28841 [90] Aggregatibacter actinomycetemcomitans Proteome LC-MS/MS analysis PRIDE archive PXD000411 [91] Candida albicans Proteome LC-MS/MS analysis PRIDE archive PRD000640 [92] Pseudomonas bacteria are reported to involve TCS system in regulation of biofilm formation. Apart from the aforementioned bacterial regulatory pathways, the EPS matrix of various bacteria are found to share similar components and further studies in EPS may provide broad-spectrum drug targets for combating mature polymicrobial biofilm [113,114].…”
Section: • • C-di-gmp Signalingmentioning
confidence: 99%